Contrasting diurnal impacts of vapor pressure deficit on water use efficiency in two semiarid steppe ecosystems - Haoran Xie; Shichao Tian; Fei Li; Jiali Sun; Xinmiao Hu; Haihua Bai; Changliang Shao (Ecological Processes)
Abstract Background Water use efficiency (WUE), a pivotal metric of carbon–water coupling strength in terrestrial ecosystems, is strongly regulated by vapor pressure deficit (VPD), yet its diurnal dynamics under contrasting water availability remain unclear. Methods Using half-hourly eddy-covariance data from a wetter meadow steppe (MS) and a drier typical steppe (TS) in Inner Mongolia, we examined how VPD regulates WUE across diurnal dynamics. Results Both steppe ecosystems exhibited a distinct U-shaped diurnal pattern of WUE during the growing season, with the lowest values occurring at midday. Although both steppes adopted a similar water-use strategy in the morning, their behaviors diverged in the afternoon. The MS significantly increased water consumption to maintain photosynthesis, leading to a decrease in WUE. In contrast, the TS showed a decoupling between VPD and WUE due to soil moisture depletion; evapotranspiration became unresponsive to elevated VPD, resulting in a slight increase in WUE instead. Additionally, a significant asynchrony between the tipping points of VPD and WUE was observed, with this mismatch being more pronounced in the TS due to intensified water limitations. Conclusions Our results indicated that soil moisture modulated the influence of VPD on WUE. In the MS, ample moisture amplified afternoon stomatal regulation of WUE, whereas in the TS, declining soil moisture weakened the effect of VPD on WUE. Under future climate warming scenarios, grassland ecosystems are likely to shift toward more water-conserving strategies, which may improve WUE to some extent but could also lead to a reduction in carbon uptake capacity. These findings highlight the need to strike a balance between enhancing WUE and maintaining ecosystem productivity.